1998
DOI: 10.1021/ac980328z
|View full text |Cite
|
Sign up to set email alerts
|

Height Equivalent to a Theoretical Plate Theory for Rectangular GC Columns

Abstract: The theory for the height equivalent to a theoretical plate (HETP) of a miniature rectangular gas chromatographic (GC) column is developed in analogy to Golay's theory for an open tubular GC column. The HETP is similar to that for an open tubular column except for the nonequilibrium or mass-transfer term. Unlike prior theories, the nonequilibrium or mass-transfer term is complexly related to column geometry. The theory successfully predicts the performance of fast chromatography, in the form of both short micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 48 publications
2
59
0
Order By: Relevance
“…Theories [14,15] for determining the HETP of a chip column have been developed. Spangler reported HETP of rectangular channel [11], as shown in (3).…”
Section: Evaluation Of Chip Columnmentioning
confidence: 96%
See 1 more Smart Citation
“…Theories [14,15] for determining the HETP of a chip column have been developed. Spangler reported HETP of rectangular channel [11], as shown in (3).…”
Section: Evaluation Of Chip Columnmentioning
confidence: 96%
“…Theory of height equivalent to a theoretical plate (HETP) of rectangular channel of chip columns was reported by Spangler. [11] His model of chip columns is compared with experimental results obtained by the chip columns.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, a parallel-plate geometry with w h is assumed, which implies that the velocity profile in the mobile phase becomes completely flat along the y-axis, except for the two boundary layers near the walls at y = −w/2 and y = w/2 [27,38,39]. In fact, the average flow velocity in a rectangular channel of the width w = 10h differs by only 6% from that in an infinitely wide channel of the same height h at the same pressure [40].…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…(11) have been reported that rely on different approximations or boundary conditions [25][26][27][28][29][30][31][32][33]. It has been shown that additional contributions to HETP are generated at the side-walls of rectangular channels when these channels have a finite width [25][26][27][28][29][30][31][32][33].…”
Section: Theoretical Sectionmentioning
confidence: 99%
See 1 more Smart Citation